KEMANDIRIANÂ ANAKÂ KELOMPOKÂ AÂ TAMANÂ KANAKâ€KANAKÂ MANDIRIÂ DESAÂ SUMBERÂ ASRIÂ KECAMATANÂ NGLEGOKÂ KABUPATENÂ BLITARÂ - naili saida (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
This study aims to describe the child's independence in group A of Mandiri kindergarten Blitar. This study uses descriptive qualitative research. His research interests are as many as 10 children in group A of Mandiri kindergarten. The data analysis technique consisted of qualitative data analysis and descriptive. Qualitative data analysis using the techniques according to Miles and Huberman consisting of data reduction, data display, and verification collected through independence instruments, interviews, field notes, and documentation. From this research it is known that the independence of children in group A Mandiri kindergarten implanted through intervention, habituation and reinforcement. Keywords: Independence, group A of Mandiri Kindergarten